2008
DOI: 10.1128/aem.02536-07
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of a New Method for Calculating Signal-to-Noise Ratio for Microarray Data Analysis

Abstract: Signal-to-noise-ratio (SNR) thresholds for microarray data analysis were experimentally determined with an oligonucleotide array that contained perfect-match (PM) and mismatch (MM) probes based upon four genes from Shewanella oneidensis MR-1. A new SNR calculation, called the signal-to-both-standard-deviations ratio (SSDR), was developed and evaluated, along with other two methods, the signal-to-standard-deviation ratio (SSR) and the signal-to-background ratio (SBR). At a low stringency, the thresholds of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…SNR was calculated using the SSDR method (He and Zhou 2008), m i /(s iF + s iB ) (where m equals spot intensity; s, pixel standard deviation; i, spot; F, foreground; and B, background).…”
Section: Microarray Normalization and Processingmentioning
confidence: 99%
“…SNR was calculated using the SSDR method (He and Zhou 2008), m i /(s iF + s iB ) (where m equals spot intensity; s, pixel standard deviation; i, spot; F, foreground; and B, background).…”
Section: Microarray Normalization and Processingmentioning
confidence: 99%
“…Images were then processed by ImaGene 6.0 software (BioDiscovery, El Segundo, CA, USA) in which a grid of individual circles defining the location of each DNA spot on the array was superimposed on the image to designate each fluorescent spot to be quantified. Hybridization spots with a signal-noise ratio X2.0 (He and Zhou, 2008) were kept for further analysis. Normalization among slides was performed based on the mean signals of all spots.…”
Section: Geochip Analysismentioning
confidence: 99%
“…2), demonstrating that spots on the array without specific formation of polymer yielded SNR values < 2.5. In addition, previous studies have shown that an SNR value of 3 is considered to be the minimum signal intensity for accurate quantification (Verdnick et al, 2002;He and Zhou, 2008;Park et al, 2008). Based on these observations an SNR value of 3 was established as our detection limit for positive signals (Fig.…”
Section: Specificity and Sensitivity For Pathogenic E Coli Detectionmentioning
confidence: 99%
“…Polymer formation was clearly evident only for those probes targeting virulence genes known to be present in the reference strains. Quantification of the specificity by measuring the SNR values for each probe on the array demonstrated that there was a clear distinction between signal intensities and background noise, an important aspect for data analysis and interpretation of results with DNA microarrays (Verdnick et al, 2002;He and Zhou, 2008). These results were achieved by using a 30-mer oligonucleotide probe allowing a more specific detection of the target gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation